Synthesization and Microstructural Analysis of Arenga Pinnata Fibres and Silicone Rubber for New Silicone Biocomposite Material / Siti Humairah Kamarul Bahrain ...[et al.] - Kamarul Bahrain, Siti Humairah; Mahmud, Jamaluddin; A. Rasid, Zainudin; Madete, June (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In promoting ‘green’ environment, natural fibres are widely used to replace man-made fibres such as glass fibres and carbon fibres which are not environmentally friendly especially when decomposed. This study for the first time aims to introduce new biocomposite material using Arenga pinnata fibre as filler while silicone rubber as its matrix. This study seeks the best form of fibre to attain good compatibility and fibre dispersion between matrix and filler. This soft composite possesses the hyperelastic material behaviour as silicone rubber has the ability to elongate at very large deformations. To synthesize the biocomposite, the fibres were crushed using a few methods and mixed with silicone mixture. The biocomposites were then cut and these cross-sections were observed under optical microscope and evaluated using SEM. It can be observed that a finer form of filler exhibits good filler-matrix adhesion compared to coarse fillers as voids can be formed during the curing process of the composite. An additional tensile test was conducted to assess its mechanical properties and it was found that the average ultimate tensile strength and modulus of elasticity of 8wt% Arenga pinnata – silicone biocomposite were 0.75 MPa and 0.067 MPa respectively. Without Arenga pinnata (pure silicone), the average ultimate tensile strength and modulus of elasticity were 0.85 MPa and 0.051MPa respectively. The addition of Arenga pinnata has thus improved silicone’s stiffness. In conclusion, this result proves that the proposed synthesization method has been successful.